Odpowiedzi

Najlepsza Odpowiedź!
2010-01-11T21:02:42+01:00
A) 2,2 + 12/7 + (-1,2) + (1 i 5/7) = 22/10 + 12/7 + (-12/10) + (-12/7) = 154/70 + 120/70 + (-84/70) + (-120/70) = 274/70 - 84/70 - 120/70 = 190/70 - 120/70 = 70/70 = 1

b) -3,9 + 5/8 + (-0,1) + 0,375 = -39/10 + 5/8 - 1/10 + 3/8 = -312/80 + 50/80 - 8/80 + 30/80 = -262/80 - 8/80 + 30/80 = -270/80 + 30/80 = -300/80 = -3,75

c) 6 i 1/2 + (-3,25) + (-1 i 3/4) + 1 = 6 i 1/2 + (-3 i 1/4) + (-1 i 3/4) + 1 = 6 i 2/4 - 3 i 1/4 - 1 i 3/4 + 1 = 3 i 1/4 - 1 i 3/4 + 1 = 3 i 2/4

d) -(-(-3) + (-2)) + (-(-3)) = -(-(-3 -2)) + (-(-3)) = -(-(-5)) + 3 = -5 + 3 = -2
2010-01-11T21:14:05+01:00
A)2,2+12/7+(-1,2)+(-1 cała i 5/7)=3 6/70 - 1,2 -1 5/7= 4 2/7 - 1 5/7=
2 całe i 4/7


c)6½ +(-3¼)+(-1¾)+1=6½-5=1½


d)-(-(-3)+(-2))+(-(-3))= -3-2+3 = -5+3 = -2